Avaliação do efeito terapêutico da dieta rica em fibra na colite experimental induzida por sulfato de sódio dextrana - Ana Letícia Malheiros Silveira (2013)
Inflammatory Bowel Diseases, including Crohns disease and Ulcerative Colitis, have an important impact on global health and their incidence has increased considerably around the world. It is believed that an imbalance of gut microbiota is associated with the development of IBD in susceptible individuals. Consumption of prebiotics could be an alternative to modulate intestinal bacterial communities which could lead to amelioration of inflammatory responses in the gut. Pectin is a dietary soluble fiber which is fermented at the colon and has prebiotic properties. The aim of this study was to evaluate the effect of a pectin-rich diet, used as a pre-treatment and as therapy in murine models of colitis induced by dextran sulfate sodium (DSS). In BALB/c with acute colitis, the pre-treatment with high fiber diet substantially improved the clinical signs of disease (clinical score and weight loss), colon length, reduced neutrophil recruitment and mucosal epithelial lesion, when compared to mice fed with conventional chow. This improvement was reflected in survival. Mice pre-treated with high pectin diet presented 100% of survival, while animals fed with chow diet had only 40% survival after DSS (4%) treatment. The high pectin diet had similar effect on clinical and histopathological parameters to pre-treatment with acetate (a short chain fatty acid with anti-inflammatory property) in acute colitis. In a chronic model of colitis induced by DSS (3%), animals pre-treated with the high pectin diet improved clinically and maintained colon length, reduced eosinophil peroxidase activity (EPO) and had greater levels of interleukin (IL)-6 and IL-10 in the colon. When treatment with high fiber diet was started after disease was established (at cycles 3, 4 or 5 of DSS), there was only a partial effect on EPO and colon weight compared to animals fed with chow diet. Other clinical and laboratory parameters were unaltered. In conclusion, treatment with high fiber diet had major effects on the outcome of colitis induced by DSS. Protective effects are mimicked by short fatty acids, suggesting a role for the generation of these molecules in the beneficial effects of the high fiber diet. However, beneficial effects are mostly seen when diet is given as a pre-treatment, suggesting that therapy aimed at modifying the gut environment (e.g. prebiotic and probiotic strategies) should be given early in the course of disease.